Should anti-EGFR mAbs be discontinued for conversion surgery in untreated right-sided metastatic colorectal cancer? A systematic review and meta-analysis - Datian Chen; Xiang Zhang; Guangyi Gao; Lili Shen; Jiaqi Xie; Xiaoping Qian; Huiyu Wang (World Journal of Surgical Oncology, 2018)
Abstract Background Previous studies have demonstrated that left-sided tumors have better prognoses than right-sided tumors in RAS wild-type mCRC (metastatic colorectal cancer) patients, while anti-EGFR mAbs appear to have no advantage compared with bevacizumab for right-sided tumors in these patients. Nevertheless, it remains unclear whether primary tumor location affects patients’ options for potentially curative resection. Methods PubMed, the Cochrane Library, Embase, ASCO, and ESMO conference abstracts were searched. The inclusion criteria were RCT (randomized controlled trials) studies that evaluated the efficacy of anti-EGFR mAbs based on primary tumor location. The outcomes included ORR, ETS, and DpR. ORs for ORR were calculated with 95% confidence intervals by Comprehensive Meta-Analysis, version 2.0. Result Nine studies including nine RCTs were analyzed. Regardless of left- or right-sided tumors, the ORRs for anti-EGFR mAb (left-sided: 80.2%, 95% CI, 47–95%; I 2 = 76.9%; right-sided: 46.1%, 95% CI, 39.4–53.0%; I 2 = 18.9%) were both higher than the control arm including chemotherapy with or without bevacizumab. The ORs for anti-EGFR mAbs have a significant benefit compared with chemotherapy with or without bevacizumab in left-sided tumors (OR = 2.19, 95% CI, 1.41–3.38; P < 0.001). For right-sided tumors, anti-EGFR mAbs still significantly improved the ORR compared with chemotherapy alone (OR = 1.75, 95% CI, 1.05–2.90; P = 0.03), and the OR numerically favored the anti-EGFR mAbs compared with bevacizumab (OR = 1.281, 95% CI, 0.77–2.12; P = 0.335). The data of ETS and DpR from three RCTs also favored the EGFR antibody irrespective of tumor location. Resection data on differentiating tumor locations is inconclusive. For right-sided tumors, it should be noted that median PFS and OS were comparable for patients who achieved ETS in both treatment arms. Conclusions Anti-EGFR mAbs have advantages in the tumor shrinkage regardless of left- or right-sided tumors, which is important for conversion therapy. For right-sided tumors, anti-EGFR mAbs should remain the first choice for potentially curative resection in RAS wild-type mCRC patients. ETS may represent a subgroup of patients with right-sided tumors who might benefit from the anti-EGFR mAb.